The relationship between safety measures, preparedness, and mental health outcomes in New York City during the COVID-19 pandemic - Thi Kim Ngan Vo; Norbert Skokauskas; Keely Cheslack-Postava; Christina W. Hoven; Christina W. Hoven (Frontiers in Psychiatry)
BackgroundThe COVID-19 pandemic necessitated strict safety measures and preparedness, potentially influencing mental well-being worldwide. This study investigated the impact of safety measures and preparedness levels on mental health outcomes during the COVID-19 pandemic in New York City, USA examining how sociodemographic characteristics modified these associations.MethodA longitudinal study of 1,227 participants from three ongoing cohorts, provided data through telephone interviews across three waves from March 2020 to August 2021. Depression and anxiety were measured using Patient Health Questionnaire 8 (PHQ-8) and Generalized Anxiety Disorder 7 (GAD-7). Logistic regression models were used to investigate associations between safety measures, preparedness, and mental health outcomes over time, adjusting for potential confounders and assessing the modification effect of demographic factors.ResultsAt Wave 1, 18% of participants reported moderate to severe depression, while 20% had moderate to severe anxiety. Over time, these rates declined significantly, with depression dropping to 9% and anxiety to 10% by Wave 3. Safety measures practiced at Wave 1 showed a protective effect on depression at Wave 3 (OR=0.45, 95% CI: 0.22, 0.91). Higher preparedness levels were significantly associated with reduced odds of anxiety (aOR=0.72, 95% CI: 0.55, 0.93) in the concurrent wave. Age specific analysis revealed that individuals aged 26-35 experienced stronger protective effects from higher preparedness levels (OR=0.43, 95% CI: 0.2, 0.92) compared to younger age groups.ConclusionThis study highlights the importance of safety measures and preparedness in mitigating mental health challenges during crises. Addressing age specific factors and preparedness levels can guide the public health strategies to better support diverse populations.